Earthquake Mitigation: An Application of Wireless Sensor Networks - Dwi Joko Suroso; Panarat Cherntanomwong; Sunarno Sunarno (Teknofisika, 2012)
The high number of victim as the result of earthquake disaster needs some intentions in the technology application. The mitigation scheme to reduce the destruction caused by earthquake is developed. This paper describes the theoretical and empirical concepts of wireless sensor networks for earthquake mitigation applications. First, the existing researches about earthquake mitigation using wireless sensor networks are explored, and a review of each technique and system is provided. Then, the influencing factors which affect the result for each technique are explained. The comparison of the efficient system for earthquake mitigation for each technique and system is emphasized.